Development of lighting system for imitating multi depth underwater light condition - Ab Azis, Fadilah; Mohd Aras, Mohd Shahrieel; Syed Abdul Hamid, Syed Mohamad Shazali; Daswir, Saiful Edwend; Ali, Fara Ashikin (2014)
This paper describes the development of the lighting system for simulating the underwater environment at different depth. The major obstacle faced by the underwater environment system is the extreme loss of colour and contrast when submerged to any significant depth whereby the image quality produced is low. The studies can easily carry out by developing the prototype of lighting system that imitates the underwater environment. Thus, suitable lighting system with the right colour options are selected where it act as an imitator for underwater environment at different depth. By using this imitator, this prototype might be able to produce image that can be comparable with the actual environment. The water tank is the best choice as the medium for imitating and it is attached with the red curtain in order to create the environment without any unwanted lighting source or disturbances. The underwater flood light is also included and it creates the scenery of the lighting underwater environment. The brightness of the light can be adjustable by adjusting the input voltage. In order to capture and record the image of the imitated underwater, the underwater camera and recordable receiver display is used. Lastly, since the underwater environment has noise the automatic pump is applied to create the ambient noise. The result shows that the appropriate combination of colour and the brightness based on different depth it may produce the precise hue and saturation with the actual environment system.